2020
DOI: 10.1016/j.toxlet.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

α-asarone induces cardiac defects and QT prolongation through mitochondrial apoptosis pathway in zebrafish

Abstract: Link to publication on Research at Birmingham portal General rightsUnless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law.• Users may freely distribute the URL that is used to identify this publication.• Users may download and/or print one copy of the publication from the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…An earlier study has reported that the natural phenylpropene, α-asarone, did not significantly affect mortality and hatching rate, whereas there was an increased malformation rate in zebrafish in a concentration-dependent pattern (Shang et al, 2020). In a similar line, we observed that Pb-exposed, and CGA, NCGA, and CCGA co-treated group exerted no effect on the hatching rate and mortality when compared with the control group.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…An earlier study has reported that the natural phenylpropene, α-asarone, did not significantly affect mortality and hatching rate, whereas there was an increased malformation rate in zebrafish in a concentration-dependent pattern (Shang et al, 2020). In a similar line, we observed that Pb-exposed, and CGA, NCGA, and CCGA co-treated group exerted no effect on the hatching rate and mortality when compared with the control group.…”
Section: Discussionsupporting
confidence: 83%
“…Developmental neurotoxicity induced by Pb was assessed as per our earlier reported study (Jin et al, 2019b;Shang et al, 2020). The mortality rate evaluated from 24 to 120 hpf was identified by coagulation of the larvae.…”
Section: Assessment Of Developmental Neurotoxicitymentioning
confidence: 99%
“…Seizures can lead to neuronal death via apoptosis and autophagy signaling pathway activation. , PTZ administration has been reported to increase cell death in the nervous system of rodent seizure models . Zebrafish larvae offer an advantage in investigating neuronal apoptosis. , We observed that SS treatment significantly inhibited the PTZ-induced increase in apoptotic cells in the zebrafish head and trunk, suggesting that this effect might be an underlying mechanism behind the anticonvulsant effect of SS.…”
Section: Resultsmentioning
confidence: 61%
“…A TUNEL assay was performed to assess apoptosis according to the protocol from our earlier reported study. , Zebrafish larvae at 7 dpf were fixed overnight at 4 °C in 4% paraformaldehyde (PFA). After washing with PBS, endogenous peroxidases were blocked by incubation in 3% H 2 O 2 in methanol for the duration of 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, cell viability was decreased when the concentration of glucose added was increased, as well as when the incubation time with HG was increased. Previous studies have reported that lncRNA TUG1 and podocytes serve an important role in the progression of diabetic nephropathy (19,20). Therefore, it was hypothesized that HG would also affect TUG1 expression in podocytes.…”
Section: Hg Reduces Tug1 Expression In Podocytesmentioning
confidence: 99%